Application of equivalent aperture method for solution of the problem of electromagnetic wave diffraction on a cylinder - Ильницкий, Л. Я.; Сибрук, Л. B.; Губернаторова, Е. И. (Proceedings of National Aviation University (archive), 1999)
Considered is the algorithm of calculation of diffraction wave tension field when it is falling on a small radius cylinder which has finite linear dimentions. The equivalent aperture method is used according to which the real aperture of field secondary sources change equivalently